ทฤษฎีและการสร้างโต๊ะตัดแผ่นเหล็กด้วยเปลวไฟ ที่ควบคุมด้วยคอมพิวเตอร์ : รายงานผลการวิจัย - วริทธิ์ อึ๊งภากรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1988)
Microcomputer is used for controlling the X-Y plane motion flame cutting table. The motion in each direction, which is orthogonal, is powered by two permanent d.c. servomotors (one in each direction). PIDP (Proportional-Integral-Derivative plus Preview) is implemented in a microcomputer to control the motion of the d.c. servomotors. The dynamics of the structure of the flame cutting table is also studies and tested experimentally to verified the mathematical model which is used for the design of the closeloop control. From the experiments, it was shown that the position errors were less than 0.70 millimeter and 0.76 millimeter for X and Y direction respectively, when the path velocity is 0.015 m/sec in circular path motion. The position errors of the path velocity range from 0.005 to 01.5 m/s have also been investigated. It is noted that the major effect for the position error is mostly dur to backlash of the gear drive unit.